Prognostic factors for survival in dogs with pituitary‐dependent hypercortisolism treated with trilostane. (10th January 2015) - Fracassi, F.; Corradini, S.; Floriano, D.; Boari, A.; Aste, G.; Pietra, M.; Bergamini, P. F.; Dondi, F.
Abstract : Pituitary‐dependent hypercortisolism (PDH) is one of the most frequent endocrinopathies in dogs, but prognostic factors are largely unknown. The aim of this retrospective case series study was to determine the prognostic value of different clinical and clinicopathological variables evaluated in dogs newly diagnosed with PDH that were subsequently treated with trilostane. Medical records from one referral centre were evaluated. Eighty‐five dogs with PDH were included. The median survival time was 852 days (range 2–3210 days); 60/85 (70 per cent) and 25/85 (29 per cent) dogs survived more than one and three years, respectively. In multivariable model analysis the length of survival of older dogs (HR 1.24, 95% CI 1.09 to 1.40) and dogs with higher serum phosphate concentrations (HR 1.35, 95% CI 1.01 to 1.81) was shorter. Serum phosphate concentrations were above the reference range in 37/85 (44 per cent) of animals. Clinical signs, liver enzymes, serum cortisol concentrations of the endocrine tests, proteinuria, systolic hypertension, the presence of concomitant disorders, and the frequency of trilostane administration were not associated with survival time. Hyperphosphataemia is a common finding in dogs with newly diagnosed PDH and represents a negative prognostic factor.